Outward FDI and the investment development path of a late-industrialising economy: Evidence from Ireland - Frank Barry; Holger Görg; Andrew MacDowell (University College Dublin, Department of Economics, 2001)
The Investment Development Path (IDP) hypothesis holds that a country's net outward direct investment position is systematically related to its level of economic development. Ireland is an interesting test case because of the importance of inward FDI over the last three decades, the country's rapid recent FDI-fuelled growth, and the recent increase in outward FDI by Irish-owned multinationals. We find empirical support for the IDP concept for the Irish case. Our sectoral analysis shows up important differences between Ireland's outward FDI and the bulk of FDI occurring in the world economy however. Ireland's outward FDI flows are as yet almost exclusively horizontal and they go largely into non-internationally-tradable manufacturing and services sectors. Also, the firmspecific assets of Irish multinationals lie neither in R&D nor in the type of product differentiation associated with high advertising expenditures.
hdl:10197/1255
Keywords: 330; outward FDI; investment development path; Ireland; Direktinvestition; Irland